A fotografia de moda e a possibilidade de transformar o corpo da moda em corpo na moda - Ortiz, Rogério D'Avila (2018)
This study sets out to problematize the expressions “fashionable body shape” and “fashion-conscious body shape” from the hypothesis that media-flooding fashion photography disseminates a homogenizing body standard that functions as a control agent, in a surveillance system, in which the model agency acts as a panopticon (Bentham).The question we raise is: how to make bodies domesticated by what fashion photography disseminates in the media unique again (Foucault, 1975)? The goal is to show that a model-subject can cease to be a mere tool for maintaining what has been cemented in beautiful, lifeless bodies. To that end, a methodology was developed to turn this vulnerability into power. Models and photographers were heard, experiments were conducted, and recent occurrences are narrated within the fashion context, in which the mediatization of a certain body type can be observed. The theoretical foundation is mainly supported by the Bodymedia Theory (KATZ and GREINER) to explain the body-environment relationship, and by Sibila (2016), to deal with some of the body’s communication processes. The relevance of this study is justified by the fact that in order to change the status quo, it is necessary to provide information where it is not available